Assessing the Potential Impact of a Long-Acting Skin Disinfectant in the Prevention of MRSA. (October 2020) - Lofgren, Eric
Abstract : Background: Healthcare-associated transmission of methicillin-resistant Staphylococcus aureus (MRSA) remains a persistent problem despite advances in prevention. The use of chlorhexidine gluconate (CHG) as a means of decolonizing patients, either through targeted decolonization or daily bathing, is a frequently used measure to supplement other MRSA reduction interventions. However, there is room for new and innovative decolonizing agents. We explored the potential utility of a long-acting CHG-like disinfectant with a persistent protective effect as well as an immediate decolonizing action in the prevention of MRSA acquisition as well as the subsequent development of clinical illness and MRSA-related mortality. Methods: We modeled MRSA transmission throughout an 18-bed intensive care unit, based on previously published models. A baseline model with no daily decolonizing protocol was used as a baseline and was compared to a scenario assuming that patients were bathed with CHG, which decolonizes them but provides no ongoing protection, as well as a scenario involving a hypothetical treatment that both decolonizes and provides ongoing protection from subsequent colonization. We varied the duration and efficacy of this protection to fully explore the potential utility of such a treatment. Results: The results of the simulations are shown in Fig. 1, where duration and efficacy of protection varied. The number of MRSA acquisitions from each combination is depicted as a single point, with blue points indicating correspondingly fewer MRSA acquisitions. Overall, improved efficacy of the hypothetical disinfectant resulted in immediate improvements in MRSA acquisition rates when compared to the baseline. To see major improvements in the MRSA acquisition rate due to the duration of infection, that duration must be well above 10 hours in many scenarios. There is also little evidence of synergy between the two. Conclusions: Based on recent results suggesting CHG has a relatively modest per-use efficacy (<.20), there is room for improvement in the formulation and administration of decolonizing agents. Although there has been considerable excitement about the possibility of long-acting agents that not only decolonize but provide long-acting protection against colonization, these results suggest that such protection would only result in markedly decreased acquisition rates only if that duration of protection was extremely long, or if the agent itself was also considerably more efficacious than CHG. These results may be used to help consider the necessary study size for clinical studies of these agents in the future, or to set research priorities and properly calibrate expectations. Funding: None Disclosures: None